The impact macroeconomic variables in Malaysia towards housing price index / Aqmalina Sazwani Samat - Samat, Aqmalina Sazwani (Faculty of Business Management, 2015)
Housing price in Malaysia nowadays is become crazily increase from year to year. This study was attempted to identify the factors that influence housing price in Malaysia. Therefore, this research is conducted in order to find out the most influential factors of housing price in Malaysia. The dependent variable in this study is housing price while the independent variables are interest rates, inflation rates and gross domestic product. Data is collected from Bursa Malaysia, Bank Negara Malaysia and also Data Stream. The research methodology uses quarterly time series data which consist of three independent variables and one dependent variable for 14 years since (2000-2013). All data were being process using EVIEWS 8 Software. The findings shows that one independent variables is significant with dependent variables while the others is not significant and all the independent variable moves in same direction which is all independent variable shows positive relationship. It means that all the independent variables have positive relationship with the dependent variable. At the same time, interest rate is the most influence factor in determining the house price fluctuation. For further studies, a wider scope is recommended where more determinant factors can be taken into research in order to obtain good result.